STRUKTUR LAPORAN KEUANGAN USAHA MIKRO KECIL DAN MENENGAH DI KOTA TERNATE - Muhammad Daud bin Mahmud (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aimed to determine the way to practice of compiling financial statements of micro, small and medium enterprise (SMEs) and to compile financial statements format based on Financial Accounting Standards for Small Medium Enterprise (SAK-EMKM) that could be applied by SMEs actors in general. This study used a qualitative method with observation and literature study approach. This study’s objects consisted of three SMEs registered at Dinas Koperasi dan UKM Kota Ternate. The results of this study found that those three respondents had constraints in accessing venture capital because they had limited knowledge in compiling the financial statements. This study is limited in compiling financial statements without comprehensive accounting cycle. For further study we suggested to add format of accounting cycle starting from recording business transactions so it would be easier for the actors of SMEs to collect information to compile financial reports.